2016
DOI: 10.4331/wjbc.v7.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Yersiniatype III effectors perturb host innate immune responses

Abstract: The innate immune system is the first line of defense against invading pathogens. Innate immune cells recognize molecular patterns from the pathogen and mount a response to resolve the infection. The production of proinflammatory cytokines and reactive oxygen species, phagocytosis, and induced programmed cell death are processes initiated by innate immune cells in order to combat invading pathogens. However, pathogens have evolved various virulence mechanisms to subvert these responses. One strategy utilized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 142 publications
(209 reference statements)
0
51
0
3
Order By: Relevance
“…находясь внутри макрофагов, бактерии синте-зируют компоненты системы секреции третьего типа (T3SS), которые многие годы были и остаются объ-ектом пристального внимания ученых [32,33]. T3SS, кодируемая плазмидой кальций-зависимости (pCD1), состоит из 25 белков, которые образуют подобную шприцу инжектисому, пронизывающую обе мембра-ны и образующую иглу на поверхности бактерий.…”
Section: Problemy Osobo Opasnykh Infektsii [Problems Of Particularly unclassified
“…находясь внутри макрофагов, бактерии синте-зируют компоненты системы секреции третьего типа (T3SS), которые многие годы были и остаются объ-ектом пристального внимания ученых [32,33]. T3SS, кодируемая плазмидой кальций-зависимости (pCD1), состоит из 25 белков, которые образуют подобную шприцу инжектисому, пронизывающую обе мембра-ны и образующую иглу на поверхности бактерий.…”
Section: Problemy Osobo Opasnykh Infektsii [Problems Of Particularly unclassified
“…Haemodialysis patients are chronically iron deficient and iron supplementation is routinely administered to maintain an iron appropriate level. Iron is an essential growth factor of bacteria for multiplication in the host, and, on the contrary, evidences showed that iron supplementation is harmful for the host defence mechanisms, oxygen transport, deoxy ribonucleotide synthesis, and redox reactions (6,28,35). In haemodialysis patients, various authors reported high incidence of iron-overload (8,13,26).…”
Section: Introductionmentioning
confidence: 99%
“…In haemodialysis patients, various authors reported high incidence of iron-overload (8,13,26). Y. enterocolitica requires iron for growth and it is able to accelerate the proliferation using exogenous chelators as source of iron in patients showing an iron-overloaded state or receiving an iron-chelating therapy (6,13,26,28). Y. enterocolitica group is traditionally divided in 6 biogroups based on phenotypic features, and into more than 57 O serogroups based on their (9).…”
Section: Introductionmentioning
confidence: 99%
“…Comparable to YopJ, YopM has been shown to block mature caspase-1 activity inhibiting the recruitment of pro-caspase-1 to the inflammasome complex [32][33][34]. Loss of the T3SS or the pCD1 plasmid results in complete attenuation of all three pathogenic species in mice [18]. This further validates the importance that the T3SS is vital for the virulence of the bacteria.…”
Section: Evasion Of the Immune Response By The Ysc Type III Secretionmentioning
confidence: 59%
“…YpkA/YopO, YopE, YopT and YopH play a role in the disruption of the actin cytoskeleton and target eukaryotic cell signaling components of the RhoA family of small GTPases that facilitates the inhibition of phagocytosis with the exception of YopH for the later [17,18]. Additionally, YopH disrupts both the innate and adaptive immunity pathways that are important for the virulence of all three pathogenic species in mice [17,19], in addition to inhibiting autophagy and blocking phagocytosis in macrophages [17,20,21].…”
Section: Evasion Of the Immune Response By The Ysc Type III Secretionmentioning
confidence: 99%